2021
DOI: 10.3390/ijms22094635
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Surfactant Protein D as a Biomarker for Evaluating Pulmonary Toxicity of Nanomaterials in Rat

Abstract: This work studies the relationship between lung inflammation caused by nanomaterials and surfactant protein D (SP-D) kinetics and investigates whether SP-D can be a biomarker of the pulmonary toxicity of nanomaterials. Nanomaterials of nickel oxide and cerium dioxide were classified as having high toxicity, nanomaterials of two types of titanium dioxides and zinc oxide were classified as having low toxicity, and rat biological samples obtained from 3 days to 6 months after intratracheal instillation of those n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, SP‐D is a secreted protein produced by type II alveolar epithelial cells and club cells, 26 so their persistently elevated levels in BALF indicate that type II alveolar epithelial cells are under sustained stimulation. 27 The HE‐stained images of the pathology in this study showed hyperplasia of type II alveolar epithelium‐like cells peaking at 3 days after intratracheal instillation, and the hyperplasia persisted although DAD reduction was also reduced, suggesting that SP‐D may be produced from these increased alveolar epithelial cells. The difference in persistence of ALP and SP‐D may have been due to the former's release due to injury and the latter's release due to injury and the increase in cells produced by the repair process after that injury.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…On the other hand, SP‐D is a secreted protein produced by type II alveolar epithelial cells and club cells, 26 so their persistently elevated levels in BALF indicate that type II alveolar epithelial cells are under sustained stimulation. 27 The HE‐stained images of the pathology in this study showed hyperplasia of type II alveolar epithelium‐like cells peaking at 3 days after intratracheal instillation, and the hyperplasia persisted although DAD reduction was also reduced, suggesting that SP‐D may be produced from these increased alveolar epithelial cells. The difference in persistence of ALP and SP‐D may have been due to the former's release due to injury and the latter's release due to injury and the increase in cells produced by the repair process after that injury.…”
Section: Discussionmentioning
confidence: 53%
“…The pathological finding in the lungs is DAD, which peaks after 3 days and then declines, consistent with the trend of ALP. On the other hand, SP‐D is a secreted protein produced by type II alveolar epithelial cells and club cells, 26 so their persistently elevated levels in BALF indicate that type II alveolar epithelial cells are under sustained stimulation 27 . The HE‐stained images of the pathology in this study showed hyperplasia of type II alveolar epithelium‐like cells peaking at 3 days after intratracheal instillation, and the hyperplasia persisted although DAD reduction was also reduced, suggesting that SP‐D may be produced from these increased alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latest technologies allowing noninvasive measurement of carboxyhemoglobin using pulse CO-oximeter can be used at the site of injury for early diagnosis of inhalation injury. 12…”
Section: Diagnosismentioning
confidence: 99%
“…Additionally, blood gas analysis, carboxyhemoglobin levels, and biomarkers such as surfactant protein-D may aid in assessing the severity and progression of inhalation injury. 12 Despite large amount of clinical and basic science research studies being published, there is no consensus on the diagnostic criteria for inhalation injury. It differs between the burn centers and hospitals.…”
Section: Diagnosismentioning
confidence: 99%
“…The intratracheal instillation of high-toxicity (nickel oxide and cerium dioxide) and low-toxicity (titanium dioxides and zinc oxide) nanomaterials was conducted and rat biological samples (blood and BALF) taken from 3 days to 6 months after installation were collected. The results indicated that the expression of SP-D in serum and BALF depended on the level of lung inflammation and that SP-D can serve as a biomarker for evaluating the pulmonary toxicity of nanomaterials [ 10 ]. Another study investigated the impact of copper-titanium dioxide nanocomposite (Cu/TiO 2 -NC) on bacteria viability, antioxidant enzymes, and fatty acid profiling.…”
mentioning
confidence: 99%